2022
DOI: 10.1088/1742-5468/ac603a
|View full text |Cite
|
Sign up to set email alerts
|

Changeover phenomenon in randomly colored Potts models

Abstract: A hybrid Potts model where a random concentration p of the spins assume q 0 states and a random concentration 1 − p of the spins assume q > q 0 states is introduced. It is known that when the system is homogeneous, with an integer spin number q 0 or q, it undergoes a second or a first order transition, respectively. It is argued that there is a concentration p* such that the transition nature of the model is changed at p*. This idea is demonstrated analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…It was shown that the model exhibits a first-order phase transition when the number of "molecule states" is high [25]. An interesting is the case of a hybrid Potts model [26]. Within 𝑞 𝑐 states, it introduces two subsets of states, that can be occupied with different probability.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the model exhibits a first-order phase transition when the number of "molecule states" is high [25]. An interesting is the case of a hybrid Potts model [26]. Within 𝑞 𝑐 states, it introduces two subsets of states, that can be occupied with different probability.…”
Section: Introductionmentioning
confidence: 99%